2020
DOI: 10.15586/jrenhep.2020.61
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Safety of a Newly Formulated Pirfenidone in Chronic Kidney Disease: A Non-Randomized Pilot Study in Mexican Patients

Abstract: The aim of this pilot clinical trial was to evaluate the safety of a new formulation of prolonged-release Pirfenidone (PR-PFD) in chronic kidney disease (CKD), specifically focal and segmental glomerular hyalinization (FSGH). Open-label, pilot, nonrandomized trial. Eighteen patients previously diagnosed with CKD stages 1– 5 according to “Kidney Disease: Improving Global Outcomes” were enrolled in the study. Target dos-age of PFD was 1200 mg twice a day in the form of prolonged-release tablets to reach a full d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Pirfenidone is able to inhibit tubular epithelial-mesenchymal transition (EMT) and renal fibrosis. Pirfenidone is also capable to reduce cellular proliferation in vivo and in vitro through downregulating the MAPK pathway (13)(14)(15)(16)(17)(18). Chen et al showed that pirfenidone inhibits caspase-9 and caspase-3 cleavage in renal proximal tubular cells and inhibited apoptosis of epithelial tubular cells in a dosage-dependent fashion.…”
Section: Mechanism Of Action Of Pirfenidonementioning
confidence: 99%
See 1 more Smart Citation
“…Pirfenidone is able to inhibit tubular epithelial-mesenchymal transition (EMT) and renal fibrosis. Pirfenidone is also capable to reduce cellular proliferation in vivo and in vitro through downregulating the MAPK pathway (13)(14)(15)(16)(17)(18). Chen et al showed that pirfenidone inhibits caspase-9 and caspase-3 cleavage in renal proximal tubular cells and inhibited apoptosis of epithelial tubular cells in a dosage-dependent fashion.…”
Section: Mechanism Of Action Of Pirfenidonementioning
confidence: 99%
“…This new pharmaceutical formulation of pirfenidone displayed minor side effects and increased tolerance compared to pirfenidone preparations used in previous studies. Prolonged release pirfenidone can safely be administered as an adjuvant therapy in patients with CKD (18).…”
Section: Pirfenidone In Renal Fibrosismentioning
confidence: 99%